Penerapan Metode 5s Terhadap Lingkungan Kerja Pada Proses Pembuatan Bubuk Kopi (Studi Kasus: UD Fauzi Ibrahim B Meulaboh) - Rita Hartati; Yusi Hidjrawan; Marlinda Marlinda (Jurnal Optimalisasi, 2026)
The rapid development of the industrial world demands business owners to increase their competitiveness through operational efficiency and labor productivity, where the work environment stands as a crucial determining factor. This study aims to analyze the implementation of the 5S method (Seiri, Seiton, Seiso, Seiketsu, and Shitsuke) and assess its effectiveness in improving the work environment conditions during the coffee powder production process at UD. Fauzi Ibrahim B, Meulaboh. The research employs a descriptive design with a mixed-methods approach , utilizing direct observations, semi-structured interviews, Likert-scale questionnaires, and documentation for data collection. Using a total sampling technique (census), 4 respondents consisting of the business owner and production workers were selected. The results indicate that three 5S elements—Seiri (Sorting), Seiso (Shining), and Seiketsu (Standardizing)—achieved maximum effectiveness at 100% (Effective category). However, the other two elements, Seiton (Setting in Order) and Shitsuke (Sustaining), reached only 50% (Moderately Effective category) due to unoptimized tool grouping and an unstructured culture of workplace discipline. In conclusion, while the technical aspects of 5S are functioning well, the managerial aspects remain weak and require improvement through standard operating procedures (SOPs), routine cleaning schedules, tool labeling, and enhanced continuous supervision.